‘Choice of law for formation of contracts: Solomon Lew v Kaikhushru Shiavax Nargolwala - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2021)
The appropriate choice of law rule for the formation of a contract is an intractable question. Various solutions have been offered, with none enjoying universal approval. In Solomon Lew v Kaikhushru Shiavax Nargolwala, the Singapore Court of Appeal held in favour of the application of a nuanced version of the putative proper law of a contract. It further held that that there was no role for the lex fori in resolving this classic conflict of laws conundrum. While the SGCA emphasised that the reasonable expectations of the parties would be accommodated through its approach, this note argues that this would not necessarily be the case and that the SGCA was too quick to discount a role for the lex fori.